Pengaruh Pendekatan Pembelajaran dan Gender Terhadap Pemahaman, Kesenangan, dan Keterampilan Bermain Sepak Bola Pada Siswa SMP - Sucipto; Beltasar Tarigan; Amung Ma'mun; Yunyun Yudiana (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2021)
The purpose of this study was to determine the effect of the learning approach and gender on increasing understanding, enjoyment, and soccer playing skills. An experimental method with a factorial design was used in this study. The total sample was 60 students consisting of 30 boys and 30 girls. The instrument used is a questionnaire of comprehension scale, pleasure scale with modified PACES test and a soccer playing performance test. Data analysis will be presented in the form of standard deviations and average values using SPSS version 24. The results of the research approach to learning, Interaction of Approaches with Gender have a significant effect on increasing students' understanding, enjoyment, and skills in playing football. So that the tactical approach is considered as an effective way to increase the understanding, enjoyment, and skills of playing football for junior high school students